Advances in geophysics. - Dmowska, Renata (Advances in geophysics, 2014)
The critically acclaimed serialized review journal for over 50 years, Advances in Geophysics is a highly respected publication in the field of geophysics. Since 1952, each volume has been eagerly awaited, frequently consulted, and praised by researchers and reviewers alike. Now in its 55th volume, it contains much material still relevant today--truly an essential publication for researchers in all fields of geophysics. Key features: * Contributions from leading authorities * Informs and updates on all the latest developments in the field.